2021
DOI: 10.7251/ace2134169m
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Economy in Nigeria: A Quantitative Approach

Abstract: This study has examined the potential impacts of climate change on Nigerian economic growth using a time series data (1980-2017). In doing so, an econometric model has been constructed based on theoretical and empirical literatures of the climate change economics, then it has employed a growth model adapted from the Solow growth model. The research work found that annual average rainfall has a significant effect on economic growth both short-run and long-run. Also, there is a high degree of positive and signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…These results are consistent with the research conducted by Jonathan and Emmanuel (2017) and Kareem et al (2022), who also concluded that carbon emissions significantly adversely impact short-term EG. However, these results contradict the findings of Adejumo (2021), who identified a significant positive relationship between carbon emissions and economic growth.…”
Section: Discussion Of Findingscontrasting
confidence: 99%
See 3 more Smart Citations
“…These results are consistent with the research conducted by Jonathan and Emmanuel (2017) and Kareem et al (2022), who also concluded that carbon emissions significantly adversely impact short-term EG. However, these results contradict the findings of Adejumo (2021), who identified a significant positive relationship between carbon emissions and economic growth.…”
Section: Discussion Of Findingscontrasting
confidence: 99%
“…Conversely, a negative relationship was observed between net migration and EG. Regarding Granger causality, the results indicate no causality between climate change and economic growth, which contrasts with the findings of Kareem et al (2022) and contradicts the results of Adejumo (2021), who found a unidirectional causality between annual average rainfall and economic growth in Nigeria.…”
Section: Discussion Of Findingscontrasting
confidence: 86%
See 2 more Smart Citations